2-Deoxy-D-glucose ameliorates inflammation and fibrosis in a silicosis mouse model by inhibiting hypoxia-inducible factor-1α in alveolar macrophages - Yuting Lu; Min Mu; Xiaotian RenChen; Wenyang Wang; Yingrui Zhu; Meiping Zhong; Yuerong Jiang; Xinrong Tao (Ecotoxicology and Environmental Safety, 2024)
Inhaling silica causes the occupational illness silicosis, which mostly results in the gradual fibrosis of lung tissue. Previous research has demonstrated that hypoxia-inducible factor-1α (HIF-1α) and glycolysis-related genes are up-regulated in silicosis. The role of 2-deoxy-D-glucose (2-DG) as an inhibitor of glycolysis in silicosis mouse models and its molecular mechanisms remain unclear. Therefore, we used 2-DG to observe its effect on pulmonary inflammation and fibrosis in a silicosis mouse model. Furthermore, in vitro cell experiments were conducted to explore the specific mechanisms of HIF-1α. Our study found that 2-DG down-regulated HIF-1α levels in alveolar macrophages induced by silica exposure and reduced the interleukin-1β (IL-1β) level in pulmonary inflammation. Additionally, 2-DG reduced silica-induced pulmonary fibrosis. From these findings, we hypothesize that 2-DG reduced glucose transporter 1 (GLUT1) expression by inhibiting glycolysis, which inhibits the expression of HIF-1α and ultimately reduces transcription of the inflammatory cytokine, IL-1β, thus alleviating lung damage. Therefore, we elucidated the important regulatory role of HIF-1α in an experimental silicosis model and the potential defense mechanisms of 2-DG. These results provide a possible effective strategy for 2-DG in the treatment of silicosis.